(3PNjQg GdCYdGe HJhGQjN GdNdaGA GdCYdGe hCeQGA eUQ GdMcGe hbVGI bVGJgG aj GdCMcGe ef aJMgG GdGSdGei GdYeQi dRef fGXegGs - (3CMeO Hf SYO GdOjf GdZeQi GdYKeGfj GdTGaYjs; (3GdZeQj , CMeO Hf SYO GdOjf GdYKeGfj GdTGaYj,J (B1050 (3g` s ((3Ydi Hf CMeO Hf eMeO Hf YHO GdZfi GdOejGWi GdTGaYi s)
(3ChdgG (B:s
(3bO Ndb GdeSLO HGdYHjQ hUhJg CNaV HGdJcHjQ s
(3GfXQ GdbSe GdKGfi HQbe (B667s
(3fGbUI ef ChdgG HebOGQ (B10 (3hQbGJs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs